A Thriving Hub of Minority Islamic Education in Blackburn, England - Hanani, Nurul; Albshkar, Hajer Abdallah (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This research project examines the learning strategy employed by Tauheedul Islam Girls' High School and Sixth Form College (TIGHS) in Blackburn, England, in adapting to government policies and minority conditions. The British government policy provides Islamic schools with the autonomy to develop integrated home learning curricula. A qualitative approach was employed, with the data taken from documentary sources, supported by secondary sources in the form of reports. The findings demonstrate that TIGHS has developed a strategy for adapting to the distortive government policies by integrating Islamic teachings into the national curriculum in a home learning environment. In consideration of the individual needs of the students, the learning material is not taught in formal class units and can be used selectively, with the assistance of home tutors. The implications of home education are that students can gain valuable life experience, which is reflected in their mindset and social behaviour.